La influencia del artículo inglés a los iraquíes que estudian el español ( un estudio analítico , estadístico ) (Journal of the College of Languages (JCL), 2013)
Each language in the world has its special methods in using articles that connected with nouns. There are languages do not have articles and others their articles from one class, that is to say it do not have masculine and feminine such as our Arabic language. Also in some languages the nouns come after article.The main aim in our research is to analyze the usage of these articles and its presence or not in the structure of sentence for the learners of Spanish language as a foreign language. The usage of these articles in Spanish language forms one of the problems that face students in the grammar of Spanish language, at the same time it stands as a problem in translation because the use of Spanish articles differs radically from the use of articles in Arabic and English. The articles in Spanish are masculine and feminine, singular and plural, and each one has special role. This research identifies the difficulty of using articles and the influence of English studying on Iraqi students who are studying Spanish.We choose a group of Spanish language students as well professors and clients from Spanish department to translate a set of English sentences in to Spanish language, and after analyzing the results we have this outcome;1- The number of wrong answers for the sentences that have articles or not are 12 from 50 sentences, or 24% 2- The number of wrong answers for using articles the definite or indefinite is 8 from 50 sentences, or 16%3- The number of wrong answers for using articles masculine and feminine is 13 from 50 sentences, or 26%4- The number of wrong answers for using articles is 4 from 50 sentences, or 8%5- The number of leaving sentences with out translation is 13 from 50 sentences, or 26%